Synthesis of a New Heterocyclic System: Pyrimidine Structural Analogues of Natural Integrastatins A, B - Chikunov, Semyon Y.; Pustolaikina, Irina A.; Gatilov, Yuriy V.; Kulakov, Ivan V. (Synlett, 2024)
In this paper for the first time, we report a simple one-step synthesis of 5-methyl-11,12-dihydro-5H-5,11-epoxybenzo[7,8]oxocino[4,3-d]pyrimidine derivatives by acid-catalyzed cyclization reaction of various 4-methyl-5-acetyl pyrimidine derivatives with salicylic aldehyde. It was shown that 2-substituted 4-methyl-5-acetylpyrimidines successfully react to form a cyclization product. At the same time, 4-methyl-5-acetylpyrimidines with a substituent in the 6th position do not enter into the cyclization reaction. This may be caused by the negative effect of substituents in the 6th position, which hinder the free rotation of the acetyl group and prevent the formation of a stable pre-reaction complex. The structures of the obtained 5-methyl-11,12-dihydro-5H-5,11-epoxybenzo[7,8]oxocino[4,3-d]pyrimidine derivatives were confirmed using 1H NMR and 13C NMR spectroscopy, mass spectrometry, and X-ray diffraction analysis.
Keywords: integrastatins; 4-methyl-5-acetyl derivatives of pyrimidine; salicylic aldehyde; intramolecular cyclization; epoxybenzo[7,8]oxocino[4,3-d]pyrimidines